Horatian moments in Ovid's career and the end of Fasti 6 - Trimble, G (Oxford University Press, 2024)
This chapter is a piece of teaching-led research (a Heyworth phrase): it stems from my experience of teaching Ovid, and specifically Fasti 6, after having been taught Horace. As I worked with students who had written essays on closure in the Fasti, I found myself repeatedly articulating the kind of understanding of Horace’s final ode that I shall outline below, and encouraging them to see that much more might be implied by Ovid’s allusion to it in the last line of Fasti 6 than simply the sense of an ending. I am grateful to the editors of this volume for the opportunity to explore in writing the ideas I had been trying out in tutorials, and to connect them with a ‘Horatian’ interpretation of aspects of Ovid’s exile poetry which I had also been keeping in mind, and discussing with colleagues and students, for some years; I would like to thank the editors, too, for their advice on this chapter. But above all I am grateful to Steve for teaching me so much both formally and informally, and I ask for his forbearance if I include in what follows more about ‘late Horace’ in full Augustan flow than he would normally have the taste for.